2019
DOI: 10.1103/physrevmaterials.3.063603
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals forces stabilize low-energy polymorphism in B2O3 : Implications for the crystallization anomaly

Abstract: The cohesive energies and structural properties of recently predicted -and never synthesized -B 2 O 3 polymorphs are investigated from first principles using density functional theory and high-accuracy many-body methods, namely, the random phase approximation and quantum Monte Carlo. We demonstrate that the van der Waals forces play a key role in making the experimentally known polymorph (B 2 O 3 -I) the lowest in energy, with many competing metastable structures lying only a few kcal/mol above. Remarkably, al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…In the AB′ and AC′ stackings, the B′ and C′ layers are generated via a translation of layer A′ by (1/3, 2/3) and (2/3, 1/3), respectively. 18MR‐B 2 O 3 AB′ is exactly the previously predicted B 2 O 3 polymorph [24] …”
Section: Resultssupporting
confidence: 85%
“…In the AB′ and AC′ stackings, the B′ and C′ layers are generated via a translation of layer A′ by (1/3, 2/3) and (2/3, 1/3), respectively. 18MR‐B 2 O 3 AB′ is exactly the previously predicted B 2 O 3 polymorph [24] …”
Section: Resultssupporting
confidence: 85%
“…we found ρ 0 =0.0263 Å −3 for -4.0 GPa, and 0.048 Å −3 for 6.0 GPa. At the experimental system density, the calculated pressure was found to be -2.0 GPa at 300 K. Such negative values are known to result from the incorporation of dispersion forces 31,32 which improve the structure and chemical bond lengths with respect to experiments in Tellurides but induce a slightly tensile character. We used density functional theory with a Grimme correction (DFT-D2 33 ) in combination with plane wave basis sets.…”
Section: A Molecular Dynamicsmentioning
confidence: 93%
“…Figure 1(b) shows the B O 2 3 sheet with planar BO 3 units that we use as second reference to define E mix . It was recently shown that the inclusion of dispersion interaction corrections to DFT calculations of planar B O 2 3 leads to energy corrections of 20-30 meV/atom [24]. To the energy scale of figure 2 this would be a correction of less than 5%.…”
Section: Resultsmentioning
confidence: 97%
“…In the literature a variety of 2D boron-oxygen structures were studied. Two-dimensional variants of B O 2 3 were proposed by Ferlat et al [12,24], with building blocks formed by planar BO 3 units (see [20] and multiple hypothetical structural models for monolayers were previously considerd [26,27]. One possible B O 2 monolayer model is shown in figure 1(c).…”
Section: Introductionmentioning
confidence: 99%